The Effect of Conceptual Learning Strategies on Acquiring Kurdish Grammar Concepts Among Sixth-Grade Students (Raparin Journal of Humanities (RJH), 2025)
This research aims to assess the effectiveness of Concept Map strategies in helping sixth-grade students acquire Kurdish grammar concepts. The study used an equivalent groups design, in which one experimental group were receiving instruction based on Concept Map strategies, whereas the other group followed traditional teaching methods. The researcher selected Piremagroon primary Co-educational school for Girls as the study site and randomly assigned two divisions: one to serve as the experimental group and the other as the control group, consisting of twenty-eight and thirty students, respectively. Firstly, the selected groups were carefully matched based on several key variables. Later, a test consisting of fourteen items was constructed, including seven multiple-choice questions as well as seven matching and error identification questions. Nevertheless, the test was thoroughly examined for its psychometric properties, including both reliability and validity measures. The experiment was conducted over a period of time extending from 22/1/2024 to 7/3/2024. It involved administering the test, correcting students’ responses, extracting relevant data, and analyzing the results by means of an independent-samples t-test. However, the results showed that the experimental group significantly outperformed the control group in acquiring grammar concepts. The researcher concluded the study by making several recommendations and suggesting valuable directions for future related research in this area.